The Determination Of The Factors And Expectations Which Affect The Utilization of Health Services In_x000D_ Women: A Qualitative Research - CÖBEK ÜNALAN, GÜLRU PEMRA; ARMAN, İKBAL HÜMAY; SARIKAYA, ÖZLEM (My University, 2020)
Aim: To determine the behaviors, expectations and experiences about health-sickness of women from society, to evaluate the socio-cultural characteristics of thesebehaviors. Method: This research is qualitative, planned as “case study”. The research is sampled as goal-oriented maximum variation and 31 women included who arebetween 17-77 with different socio-cultural characteristics. Four focused interviews were conducted. Before the study, participants were informed and a questionnairewas used to question socio-demographic characteristics. The interviews were made at participants’ houses. One interviewer and two observers was ready in eachsession. The voice recordings and observers’ notes were trasncripted. No names have been transcribed. Each of the interviews were analyzed thematically, werecommonised to reach research findings. Results: According to the analysis, there are five theme topics. 1. Physician (professionalism) characteristics affecting thechoice of doctor (skills, attitude, gender, knowledge). 2. Expectations and behaviours about services related to women's health (afraid of the examination style,expectations of confidentiality and sympathy, prejudices). 3. Reasons for choosing health institutions (attitude of health workers, gender of doctor, hospital facilities,accessibility, prejudices, queue waiting). 4. Unmet health needs and thoughts about the causes (fear of malpractice, shyness, financial impossibilities, advancedappointments). 5. Attitudes on Family Health Centers (reasons for not using: lack of equipment, crowd, existing habits, doctor’s attitude, distrust to doctor'sknowledge). The participants repeated that dental health services are the most difficult to obtain. Conclusion: Socio-cultural characteristics, health services presentationand attitude of health workers influences expectations of individuals about utilization of health services. Therefore, when planning trainings of health workers, theapplicants' health perceptions affected by the socio-cultural characteristics, learning methods which allows the development of a positive attitude and improvescommunication skills should be considered. Also, in the organization of health services, taking into account the factors affecting applicants' utilization of health serviceswill be effective for the elimination the unmet needs.

Amaç: Bu çalışma, toplumumuzdaki kadınların sağlık ve hastalık davranışlarını, beklentilerini ve bu alanda yaşadıklarını ortaya koymayı ve bu davranışların sosyokültürel özelliklerini değerlendirmeyi amaçlamaktadır. Yöntem: Araştırmamız niteliksel tipte olup, “durum çalışması” şeklinde planlanmıştır. Araştırmaya amaca_x000D_ yönelik maksimum çeşitlilik örneklemesi ile farklı sosyokültürel özelliklere sahip 17-77 yaş aralığındaki 31 kadın dahil edilmiştir. Çalışmada 7-8 kişilik dört odak grup_x000D_ görüşmesi gerçekleştirilmiştir. Çalışma öncesi katılımcılar bilgilendirilmiş, sosyo-demografik özellikleri sorgulayan bir anket uygulanmıştır. Görüşmeler katılımcıların_x000D_ bu amaç için toplandığı evlerde yapılıp, ses kayıt cihazı ile kayıt altına alınmış; kişi-yer isimleri kayıtlara geçmemiştir. Görüşmelerde bir görüşmeci, iki gözlemci hazır_x000D_ bulunmuştur. Her odak görüşme, kayıt ve gözlemci notları çözümlenerek tematik analiz edilmiş, kodlar üzerinde tartışılıp, ortaklaştırılarak bulgulara_x000D_ erişilmiştir. Bulgular: Ortaklaştırma sonrası ortaya çıkan 5 tema şöyledir: 1. Doktor seçimini etkileyen hekimlik (Profesyonellik) özellikleri (beceri, tutum, tavır,_x000D_ cinsiyet, bilgi). 2. Kadın sağlığı hizmetlerine özgü beklentiler ve davranışlar (muayene şeklinden çekinme, mahremiyet ve anlayış beklentisi, önyargı). 3. Sağlık_x000D_ kurumlarını tercih etme/etmeme nedenleri (sağlık personelinin tavrı, doktorun cinsiyeti, hastanenin imkânları, ulaşılabilirlik, önyargılar, sıra bekleme)._x000D_ 4. Karşılanamayan sağlık ihtiyaçları ve nedenlerine ait düşünceler (komplikasyon korkusu, utangaçlık, maddi olanaksızlık, ileri tarihli randevular). 5. Aile Sağlığı_x000D_ Merkezleri ile ilgili tutumlar (yararlanamama nedenleri olarak donanım eksikliği, kalabalık, var olan alışkanlık, doktorun tavrı, doktorun bilgisine güvensizlik)._x000D_ Katılımcıların ulaşmakta güçlük çektiği hizmetler içinde en sık tekrar eden ifade “diş sağlığı” olmuştur. Sonuç: Bireylerin sağlık hizmetlerinden yararlanmasını_x000D_ sosyokültürel özellikleri, sağlık hizmetlerinin sunum şekli ve sağlık çalışanlarının tutumu ile ilgili beklentileri etkilemektedir. Dolayısıyla sağlık çalışanlarının mesleki_x000D_ eğitimleri planlanırken başvuranların sağlık algısını etkileyen sosyokültürel özelliklerin dikkate alınması, iletişim becerilerini geliştiren ve olumlu tutum gelişimini_x000D_ sağlayan öğrenme yöntemlerinin kullanılması düşünülmelidir. Ayrıca sağlık hizmetlerinin örgütlenmesinde, başvuranların sağlık hizmetlerinden yararlanmasını_x000D_ etkileyen nedenlerin dikkate alınması karşılanmayan gereksinimlerin giderilmesi açısından etkili olacaktır.
Kadınlarda Sağlık Hizmetinden Yararlanmayı Etkileyen Neden ve Beklentilerin Belirlenmesi: Niteliksel Bir Araştırma